"Like, Share, Comment, " and Learn: Transformative Learning in Online Anti-Trump Resistance Communities. Issue 2 (May 2020) - Schroeder, Stephanie; Currin, Elizabeth; Washington, Elizabeth; Curcio, Rachelle; Lundgren, Lisa
This article explores adult participation in online social media resistance groups that formed after the 2016 U.S. presidential election (e.g., Indivisible), why individuals participate, and how their views of citizenship are transformed as a result of their participation. Reporting on demographic and open-ended qualitative survey data, this study describes the demographics of participants and employs inductive and deductive coding as analytic methods. Making use of transformative learning as a metatheory and coding with transformative learning typologies in mind, this article illustrates the range of learning outcomes experienced by participants. Our findings indicate the educative potential of online resistance groups, as participants deepened their understandings of democracy, grew more discerning about information shared online, developed confidence to take action, and saw themselves as newly positioned in democracy, connected and capable of making change.